Interaction of the Retinoblastoma Protein with Orc1 and Its Recruitment to Human Origins of DNA Replication - Mendoza-Maldonado, Ramiro (Public Library of Science, 2010)
BACKGROUND: The retinoblastoma protein (Rb) is a crucial regulator of cell cycle progression by binding with E2F transcription factor and repressing the expression of a variety of genes required for the G1-S phase transition. METHODOLOGY/PRINCIPAL FINDINGS: Here we show that Rb and E2F1 directly participate in the control of initiation of DNA replication in human HeLa, U2OS and T98G cells by specifically binding to origins of DNA replication in a cell cycle regulated manner. We show that, both in vitro and inside the cells, the largest subunit of the origin recognition complex (Orc1) specifically binds hypo-phosphorylated Rb and that this interaction is competitive with the binding of Rb to E2F1. The displacement of Rb-bound Orc1 by E2F1 at origins of DNA replication marks the progression of the G1 phase of the cell cycle toward the G1-S border. CONCLUSIONS/SIGNIFICANCE: The participation of Rb and E2F1 in the formation of the multiprotein complex that binds origins of DNA replication in mammalian cells appears to represent an effective mechanism to couple the expression of genes required for cell cycle progression to the activation of DNA replication.